2017
DOI: 10.18001/trs.3.2(suppl1).2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Mass-merchandise Cigar Market since the Tobacco Control Act

Abstract: Objectives This study identifies the specific product characteristics driving mass-merchandise cigar sales in the context of the changing regulatory environment. Methods Cigar sales data in US convenience stores during 2008–2015 were purchased from Nielsen’s Convenience Track system. Descriptive statistics highlight changes in the cigar market over time. Results Sales of flavored cigars increased by nearly 50% since 2008 and now make up over half of the cigar market. Fruit remains the most popular flavor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
111
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 21 publications
(22 reference statements)
2
111
0
1
Order By: Relevance
“…27,28 Reports show that Swisher Sweets and Cheyenne represented about 30% of the little cigars market. 30 …”
Section: Methodsmentioning
confidence: 99%
“…27,28 Reports show that Swisher Sweets and Cheyenne represented about 30% of the little cigars market. 30 …”
Section: Methodsmentioning
confidence: 99%
“…One of the symposium objectives was the dissemination of the current state of research and policy as discussed at this Symposium by leaders in the field of cigar tobacco science. Multiple papers from the Symposium were prepared for publication on this special sub-theme in Tobacco Regulatory Science ; 13,5 other manuscripts were invited for inclusion in this special issue. 4 Collectively, the presentations provided an overview of the cigar market, advertising, social media, and celebrity endorsements, epidemiology use patterns and trends, special use in minority populations, toxicant delivery, transition and exposure, health and exposure effects, and policy implications.…”
Section: Methodsmentioning
confidence: 99%
“…Coinciding with the increasing number of state and local regulations of flavoured tobacco product sales, concept-flavoured cigars—that is, cigars with non-characterising flavour descriptions—have appeared in the marketplace 12. A chemical analysis of 16 cigars labelled with concept descriptors (eg, Royale) showed that 14 had flavour chemical profiles comparable to those of cigars with characterising flavour descriptions 17.…”
Section: Introductionmentioning
confidence: 99%